Under three flags : reminiscences of a public servant - Huque, K. A. (Kazi Anwarul) (Dhaka : Islamic Foundation, Bangladesh, 1986)
Memoirs of a former civil servant and minister in Bangladesh, on political conditions in Bangladesh under the British, Pakistani, and Bangladeshi administrations; chiefly covers the period, 1933-1981.
"I.F. Library, 954"--T.p. verso.
Keywords: Huque, K. A; Cabinet officers -- Bangladesh -- Biography; Bangladesh -- Politics and government